Comparative genomics reveals cotton-specific virulence factors in flexible genomic regions in Verticillium dahliae and evidence of horizontal gene transfer from Fusarium - Chen, Jie-Yin (The New phytologist, 2018)
© 2017 The Authors. New Phytologist © 2017 New Phytologist Trust.